e-Funktionsgleichung lösen?

... komplette Frage anzeigen

2 Antworten

h= 0,02*e^(6k)    | :0,02

h/0,02 = e^(6k)   | ln

ln(h/0,02) = 6k *ln(e)  |:6

k= (ln(h/0,02)/6

Antwort bewerten Vielen Dank für Deine Bewertung

h(t) = 0,02 * e^6k                                           | / 0,02

h(t) / 0,02 = e^6k                                           | sechsteWurzel()

sechsteWurzel(h(t) / 0,02) = e^k                  | log()

k = log_sechsteWurzel(h(t) / 0,02)(e)           fett steht im Index

Antwort bewerten Vielen Dank für Deine Bewertung

Was möchtest Du wissen?